2014
DOI: 10.1111/iwj.12392
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in post‐reperfusion syndrome after acute lower limb ischaemia

Abstract: Ischaemia reperfusion (I/R) injury refers to tissue damage caused when blood supply returns to the tissue after a period of ischaemia. Matrix metalloproteinases (MMPs), neutrophil gelatinase-associated lipocalin (NGAL) and cytokines are biomarkers involved in several vascular complications. The aim of this study was to evaluate the role of MMPs, NGAL and inflammatory cytokines in I/R syndrome. We conducted an open label, multicentric, parallel group study, between January 2010 and December 2013. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Several papers have shown that drugs with anti‐protease activity are associated with faster and better outcomes in patients with vascular disease . In the present study, we documented that pharmacological treatment induced a decrease in MMP and NGAL levels as it has not been possible to reduce the plasma levels of MMP‐1 and MMP‐8.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Several papers have shown that drugs with anti‐protease activity are associated with faster and better outcomes in patients with vascular disease . In the present study, we documented that pharmacological treatment induced a decrease in MMP and NGAL levels as it has not been possible to reduce the plasma levels of MMP‐1 and MMP‐8.…”
Section: Discussionsupporting
confidence: 51%
“…TNF‐α is a pro‐inflammatory cytokine capable of inducing adhesion molecule and proteinase gene expression, and plays a role in the progression of several diseases. IL‐6 is a pro‐inflammatory cytokine with multiple functions, and is involved in inflammatory process as well as endothelial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has concentrated on potential IRI biomarkers; these include matrix metalloproteinases, neutrophyl gelatinase associated lipocalin, and inflammatory cytokines. 182 Compartment syndrome (CS) is a serious complication following ALI revascularisation. The tissue swelling as a result of IRI raises pressure in the limb muscles which are constrained by fascial compartments.Thus, intracompartment pressure rises as a result of swelling and may be sufficiently high to reduce perfusion of already damaged tissues.…”
Section: Recommendation 34mentioning
confidence: 99%
“…Auf zellulärer Ebene kommt es kurze Zeit nach der Gefäßverletzung und peripheren Ischämie sowie folgender Reperfusion zur Aktivierung von Monozyten und Infiltration von Makrophagen, die antigenvermittelt die frühe Immunantwort einleiten [16]. Darüber hinaus sekretieren diese Makrophagen Zytokine, wie Interleukin-1 (IL-1) und Tumor-Nekrose-Faktor-α(TNF-α), die zur Aktivierung von T-Zellen führen [17,18]. Eine Reperfusion induziert die Freisetzung von sowohl reaktiven Sauerstoffspezies (d. h. oxidativer Stress) und TNF-α aus dem Endothel, wodurch über eine NF-kB-vermittelte Transkription von Genen inflammatorische Chemokine kodiert werden [19].…”
Section: Diskussionunclassified